Shared thematic elements in photochemical reaction centers. - Golbeck, J H (1993)
The structural, functional, and evolutionary relationships between photosystem II and the purple nonsulfur bacterial reaction center have been recognized for several years. These can be classified as "quinone type" (type II) photosystems because the terminal electron acceptor is a mobile quinone molecule. The analogous relationship between photosystem I and the green sulfur bacterial (and helicobacterial) reaction centers has only recently become clear. These can be classified as "iron-sulfur type" (type I) photosystems because the terminal electron acceptor consists of one or more bound iron-sulfur clusters. At a fundamental level, the quinone type and iron-sulfur type reaction centers share a common photochemical motif in the early process of charge separation, leading to the speculation that all photochemical reaction centers have a common evolutionary origin. This review summarizes the current state of knowledge in comparative reaction center biochemistry between prokaryotic bacteria, cyanobacteria, and green plants.